Inclusive Regional Development: Implementation of the Child-Friendly Regency Policy in Bogor Regency - Aryani, Nanda Dita; Silitonga, Mala Sondang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study explores the implementation of the Child-Friendly Regency/City (KLA) policy in Bogor Regency, specifically focusing on Cluster III: Basic Health and Welfare, as part of efforts to promote inclusive regional development. The research is motivated by the high infant mortality rate in Bogor Regency—the highest in West Java with 799 reported cases—and the region’s current